2005
DOI: 10.1016/j.toxicon.2004.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the insulinotropic action of a phospholipase A2 isolated from Crotalus durissus collilineatus rattlesnake venom on rat pancreatic islets

Abstract: The ability of PLA 2 and crotapotin, isolated from Crotalus durissus collilineatus rattlesnake venom, to stimulate insulin secretion from isolated rat islets was examined. PLA 2 and crotapotin stimulated insulin secretion at 2.8 mmol/L glucose, whereas at a high glucose concentrations (16.7 mmol/L) only PLA 2 stimulated secretion. Nifedipine (10 mmol/L) did not alter the ability of PLA 2 to increase insulin secretion stimulated by a depolarizing concentration of K C (30 mmol/L). PLA 2 did not affect 14 CO 2 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
1
10
1
Order By: Relevance
“…This is in agreement with the work of Yamamoto et al (1983) and Nogueira et al (2005), which report the insulinotropic action of exogenous phospholipase A 2 from C. adamanteus and C. durissus collilineatus, in rat islets. In both instances cell viability was maintained, therefore excluding the possibility of mere leakage of insulin from cells undergoing lysis.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is in agreement with the work of Yamamoto et al (1983) and Nogueira et al (2005), which report the insulinotropic action of exogenous phospholipase A 2 from C. adamanteus and C. durissus collilineatus, in rat islets. In both instances cell viability was maintained, therefore excluding the possibility of mere leakage of insulin from cells undergoing lysis.…”
Section: Discussionsupporting
confidence: 93%
“…Exposure to PLA 2 causes hydrolysis of membrane phospholipids with the subsequent production of arachidonic acid and metabolism into lipoxygenase products which are key to elevation of cytosolic Ca 2þ levels and PLA 2 -induced insulin secretion (Persaud et al, 2007). The link between arachidonic acid and insulin secretion by C. durissus collilineatus venom was confirmed by Nogueira et al (2005) when efflux in arachidonic acid was shown to be significantly higher in PLA 2 treated islets compared to control islets. Furthermore, given that 14 CO 2 production in islets was not altered, the authors hypothesized that the increase in insulin secretion following PLA 2 exposure could not be attributed to changes in glucose metabolism.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, it was reported that sPLA 2 derived from bee venom, snake venom and porcine pancreas elicited insulin secretion in vitro, although the mechanism ShOrt repOrt ShOrt repOrt has not been fully understood. [8][9][10][11] Therefore, we also investigated the effects of exogenous sPLA 2 on insulin secretion, intracellular free Ca 2+ concentration ([Ca 2+ ]i) and lysophospholipid contents in isolated rat islets.…”
Section: Expression Of Secretory Phospholipase a 2 In Insulitis Of Humentioning
confidence: 99%